Incidence of Lumpy Skin Disease Virus with its Characterization in Vaccinated Pregnant Holstein cows in Dakahlia Governorate, Egypt - Samah Mosad; Nesma Rasheed; Hanaa Ali; Khaled El-Khabaz; Eman Shosha; Mohamed El-Diasty (German Journal of Veterinary Research)
Lumpy skin disease (LSD) is an infectious economically important viral disease of cattle. Lumpy skin disease virus (LSDV) is still circulating in Egypt, despite the annual mass vaccination with sheep pox virus vaccine by the Egyptian authorities. This study was carried out on 2 farms of pregnant Holstein cows vaccinated with Bovivax LSD-N® Vaccine (farm I) and Servac Capri-C vaccine® (farm II). After 40-60 days post-vaccination, mild clinical sings were detected in 3% of farm I cows whereas a more severe clinical infection was developed in 40% of cows in farm II. LSDV was isolated on the chorioallantoic membrane (CAM) of 11 days old emberyonated chicken egg (ECEs) and Madin Darby bovine kidney (MDBK) tissue culture. LSDV was identified in collected skin tissues by Transmission electron microscopy (TEM) and Histopathological examination. Finally, LSDV was confirmed by polymerase chain reaction (PCR) amplification of 192 base pair (bp) of P32 gene and two samples were selected for DNA sequencing. LSDV developed characteristic pock lesion in inoculated ECEs. MDBK cell culture developed prominent LSDV cytopathic effect at the 3rd passage. Viral particles were detected in the cytoplasm of both epidermal cells and dermal macrophages by TEM. Histopathological examination revealed different lesions correlated with LSDV infection age. LSDV was confirmed in all tested samples by PCR. Our strains (Dakahlia- 2020-1 and Dakahlia- 2020-2) were closely related to other Egyptian LSDV strains on GenBank with 98.2%-100% identity. The present study proved conclusive evidence that live attenuated Sheep Poxvirus vaccine poorly protect Egyptian cattle against LSDV, while LSDV Neethling strain vaccine gave a promising and sufficient protection rate.